Redesain Taman Malabar sebagai Taman Terapi di Kota Bogor - Faizah, Inas Rana; Fatimah, Indung Sitti (Jurnal Arsitektur dan Perencanaan (JUARA), 2020)
The green open space that is beneficial to reduce stress is known as a healing garden. Gardens with healing concept required in Bogor City to contain healing activity and mentally accelerate the healing progress. The purpose of this research is analyzing the results againts society preferences and the needs of healing garden. Analyzing activities by accumulating the site carrying capacity was the basis to design the healing garden. The synthesis results are recommendations of healing garden criteria. The output of this research is a site plan that displays a design that divides space based on activity needs.